2015
DOI: 10.1007/s00167-015-3761-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of femoral bone tunnel characteristics on graft-bending angle in double-bundle anterior cruciate ligament reconstruction: a comparison of the outside-in and transportal techniques

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 24 publications
(35 reference statements)
0
34
2
Order By: Relevance
“…To our knowledge, few studies so far have analyzed the in vivo GBA after ACL reconstruction during dynamic weightbearing activities and related GBAs to signal intensities. Most of the previous studies about the GBA examined the knee at only one static position by postoperative CT. 1,18,29,34,39,50,53 A cadaveric study reported that the GBA changes significantly with knee motion, 30 and this effect may be even larger when the knee is under dynamic high-magnitude loads that alter knee kinematics. During the dynamic knee motion from footstrike to the early stance phase assessed in our study, the ACL is exposed to relatively high tension, with the knee at full extension to mild flexion, 3,36,59 as well as elevated forces within the joint because of the high ground-reaction forces that occur during the weight acceptance phase of the gait cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, few studies so far have analyzed the in vivo GBA after ACL reconstruction during dynamic weightbearing activities and related GBAs to signal intensities. Most of the previous studies about the GBA examined the knee at only one static position by postoperative CT. 1,18,29,34,39,50,53 A cadaveric study reported that the GBA changes significantly with knee motion, 30 and this effect may be even larger when the knee is under dynamic high-magnitude loads that alter knee kinematics. During the dynamic knee motion from footstrike to the early stance phase assessed in our study, the ACL is exposed to relatively high tension, with the knee at full extension to mild flexion, 3,36,59 as well as elevated forces within the joint because of the high ground-reaction forces that occur during the weight acceptance phase of the gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in vivo, dynamic weightbearing activities can provide a better indication of the GBA that is likely to affect the graft than static examinations. 38,42,48 There have been only limited reports on the actual influence of the GBA on ACL grafts, 1,29 and the clinical effect of a steep GBA on graft healing in vivo is not fully understood. Graft damage or poor synovial coverage of the graft is known to occur on the femoral side in many cases.…”
mentioning
confidence: 99%
“…4,32 This method has induced a rise in imaging used to validate tunnel placement both intraoperatively and postoperatively. 3,8,9,18,20,23,27,42 The practical and clinically efficient use of imaging to validate tunnel placement is hampered by the lack of consensus on where exactly the anatomic centers of the ACL in the femur and tibia are located. There are several works that have measured the femoral ACL insertion location on cadaveric specimens; however, most articles have included only a limited number of knees, varying between 7 to 36 knees, with few measurements.…”
mentioning
confidence: 99%
“…Previously, Sim et al 25 reported that the outside-in technique showed a significantly more acute graft tunnel angle than the transportal technique, but there were no statistically significant differences in the IKDC or Tegner scores between the 2 groups. Niki et al 17 also reported that the outside-in technique provided a more acute GBA, but no significant differences were observed in the Lysholm score, pivot-shift test, or anteroposterior laxity at >2.5-year follow-up between the outside-in and transportal techniques. Moreover, Lee et al 10 demonstrated that the modified transtibial group had a lower femoral GBA and higher graft maturity, but there were no significant differences in functional outcomes.…”
Section: Discussionmentioning
confidence: 96%